Numerical Analysis on the Load Sharing Performance of Long-Short CFG Pile Composite Foundation Subjected to Rotation of Adjacent Retaining Wall. (22nd July 2021) - Uge, Bantayehu Uba; Guo, Yuancheng; Liu, Yunlong
Abstract : The stress and displacement boundary conditions of excavation retaining structures affect the deformation mechanism and movement of the retained soil mass. The soil movement disturbs the load sharing performance and structural integrity of cement-fly ash-gravel (CFG) pile composite foundations existing in the vicinity, which merits considerable research work. This article presents results from 3D finite element analyses performed to study the influence of retaining wall rotation on the load sharing characteristics of adjacent CFG pile composite foundation comprising long and short piles. To verify the numerical model, a relatively large-scale 1 g physical model test was conducted. It is revealed that to arrive at a new static equilibrium during progression of wall rotation, the percentage load sharing ratios of the long and short piles change increasingly while the load proportion carried by the upper soil reduces remarkably. The percentage load sharing characteristics of CFG pile composite foundation are more affected in immediate proximity to the wall than those located at far distance. For the foundation having 3 × 3 long and short piles placed at 3.0–15.0 m away from the wall, the location resulted in a reduction of soil bearing capacity ranging between 1.4 and 7.5% of the total imposed load while the corresponding increase in the % load borne by the long and short pile range was 0.83–4.15 and 0.59–3.36%, respectively. For the other parameters considered in this article viz. pile spacing, subsoil stiffness, cushion stiffness and thickness, and applied working load, the increment in % load sharing of the long and short pile range was 3.45–4.15, 1.3–5.79, 1.48–3.36, 4.15–4.79, and 3.67–4.15% and 3.36–4.67, 1.43–4.99, 1.48–3.36, 3.36–3.64, and 1.38–3.36% of the imposed load, respectively. Moreover, the long piles' load sharing proportion was higher than that of short piles, and peripheral piles received larger load proportion.